Complete surface reconstruction of nanoporous gold during CH4 pyrolysis. Issue 22 (25th May 2022) - Hou, Xingang; Wang, Kai; Ge, Mengke; Xi, Wei; Yuan, Wenjuan; Shen, Yongli
Abstract : Nanoporous gold (NPG) is prepared with a complete regular surface that exposes the Au {111} and {100} facets through methane pyrolysis. C species significantly affect the migration and recombination of surface atoms. Abstract : The catalytic activity and selectivity of metallic nanocatalysts can be controlled using physical and chemical methods to tune the exposed crystal facets. Nanoporous metals (NPMs) have unique bicontinuous structures, large specific surface areas, and high catalytic activities, and are widely used in the field of heterogeneous catalysis. However, owing to the complex surface topography of NPMs, it is difficult to regulate their exposed crystal facets over a large area. In this study, nanoporous gold (NPG) is successfully prepared with a complete regular surface that exposes the Au {111} and {100} facets through a methane pyrolysis reaction. The results of high-spatial and -temporal resolution in situ experiments and theoretical calculations indicate that C species significantly weaken the interaction between surface Au atoms with low coordination numbers and their surrounding atoms, which results in the migration and recombination of surface atoms. This research fundamentally clarifies the reconstruction mechanism of porous materials during methane pyrolysis and provides a theoretical basis for the targeted regulation of exposed NPM surfaces.